Racially disproportionate prison populations in the United States: an overview of historical patterns and review of contemporary issues - Sabol, William J. (Contemporary crises, 1989)
This paper reviews trends in black-white incarcerations in the North and South from 1870 to 1980. Using census data on imprisonments it finds that the degree of disproportionate imprisonment of blacks (relative to their representation in the general population) has been higher in Northern states than in Southern states from the middle of the 19th century through the present, although recently the trends have begun to converge. After reviewing explanations for the higher imprisonment rates of blacks in the North, it reviews black-white patterns of arrests and imprisonments by state for 1960, 1970 and 1980 and finds that the variations in black-white imprisonments are not fully accounted for by arrests. Finally, it comments on appropriate methodologies for examining racial differences in treatment in the criminal justice system.